Faktor-Faktor Yang Mempengaruhi Akuntabilitas Pemerintah Desa Dalam Pengelolaan Dana Desa (Studi Kasus di Kecamatan Kangkung) - Ifana Dzikriyah; Maryono (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study investigates the factors influencing accountability in the management of village funds by local governments in Kangkung District, Kendal Regency. The research is driven by the growing number of village fund mismanagement cases in Indonesia, highlighting the urgent need for improved governance. Key variables examined in this study include the use of the siskeudes application, staff competence, transparency, internal control systems, local wisdom, and organizational commitment. A quantitative approach was employed, with data gathered through questionnaires distributed to 63 respondents comprising village officials, BPD members, and community representatives. The results are expected to provide both theoretical contributions to the field of public sector accounting and practical insights for village governments to enhance financial accountability and transparency. Ultimately, the study aims to support the development of sustainable and participatory village governance.